Analisis Spasial Kriminalitas Harta Benda di Wilayah Jadetabek - Nugroho, Aditya Harin; Harmadi, Sonny Harry B. (UI Scholars Hub, 2015)
This study aims to identify the existence of spatial dependence of property crime at sub-district level in the case of Jakarta, Tangerang, Depok, and Bekasi (Jadetabek), the major metropolitan area in Indonesia over 2010 period. Empirical results by using spatial autoregressive suggest the existence of positive spatial autocorrelation of property crime in Jadetabek. We also find the determinants of property crime is related to per capita household expenditure, number of youth unemployment, number of young population, number of drags abuse case, and percentage of case solved.